Increased tower eigenfrequencies on floating foundations and their implications for large two- and three-bladed turbines - Fabian Anstock and Alois Kessler and Vera Schorbach (Journal of physics / Conference Series, 2023)
If the tower of a bottom-fixed turbine is put on a floating foundation, such as a spar, semi-submersible, or barge, its eigenfrequency increases. In the investigated case, the tower eigenfrequency rose to about twice its previous value. For bottom-fixed applications, the comparatively high blade-passing frequency of a three-blade turbine (3P) leaves a great bandwidth to design a light and soft tower with a low-enough eigenfrequency. On one of those floaters, however, the eigenfrequency of the same tower might neither be high nor low enough to avoid eigenfrequency excitation by 3P around rated speed. Due to the lower blade passing frequency of a two-bladed wind turbine (2P), the same tower eigenfrequency is high enough by default, enabling considerable material savings or at least eliminating the severe eigenfrequency excitation issue of its bottom-fixed version. Additionally, cost benefits in the whole life-cycle of two-bladed turbines remain. 20MW two- and three-bladed turbines were analyzed numerically on an upscaled version of the UMaine VolturnUS-S semi-submersible, confirming the reasoning.